Distribution of rodenticide resistance and zoonotic pathogens in Norway rats in Lower Saxony and Hamburg, Germany. Issue 3 (8th August 2012) - Runge, Martin; von Keyserlingk, Michael; Braune, Silke; Becker, Detlef; Plenge‐Bönig, Anita; Freise, Jona F; Pelz, Hans‐Joachim; Esther, Alexandra
Abstract BACKGROUND: Genetically based resistance to anticoagulants has led to increasing difficulties in the control of rodents over recent decades. The possible impact of rodenticide‐resistant rats on the infection risk of humans and livestock by zoonotic pathogens is generally unknown. Hence, in a monitoring programme in the German federal states of Lower Saxony and Hamburg, more than 500 Norway rats were analysed for both Tyr139Cys polymorphisms within the VKORC1 gene and zoonotic agents. RESULTS: Evidence of resistance was almost completely restricted to the known resistance area in southern Lower Saxony. Homozygous mutations were only found in urban areas sampled owing to the occurrence of rat control problems and were missing in bycatches of rats by muskrat trappers in rural areas. In more than 25% of the rats, zoonotic bacteria (Leptospira, Salmonella, Yersinia and Coxiella) were detected. There was no obvious correlation between the occurrence of rats carrying zoonotic pathogens and anticoagulant resistance. CONCLUSION: Zoonotic agents and genetically based resistance conferred by the Tyr139Cys polymorphism are both unevenly distributed in Lower Saxony. The study provides the basis for further studies focusing on districts with high levels of pathogens and resistance to assess the potential health risk of their combined occurrence. © 2012 Society of Chemical Industry